Classical and metaheuristic optimizations performance in an electro-hydraulic control system - Chong, Chee Soon; Ghazali, Rozaimi; Chong, Shin Horng; Ghani, Muhammad Fadli; Md. Sam, Yahaya; Has, Zulfatman (International Journal of Mechanical Engineering and Robotics Research, 2022)
Electro-Hydraulic Actuator (EHA) system is a prevalent mechanism in industrial sectors. This system commonly involving works that required high force such as steel, automotive and aerospace industries. It is a challenging task to acquire precision when dealing with a system that can produce high force. Besides, since most of the mechanical actuator performance varies with time, it is even difficult to ensure its robustness characteristic towards time. Therefore, this paper proposed the industrial’s wellknown controller, which is the Proportional-Integral-Derivative (PID) controller that can improve the precision of the EHA system. Then, an enhanced PID controller, which is the fractional order PID (FOPID) controller will be applied. A classical and metaheuristic optimization methods, which are gradient descent (GD) and particle swarm optimization (PSO) algorithm are used to obtaining the optimal gains of both controllers. In addition, to examine the tracking performance of the designed controllers, the performance of the proposed optimization algorithms is analysed. As a result, in a practical point of view, it can be inferred that the PSO algorithm is capable to generate more practical sense of gains compared with GD, and the precision characteristic of the FOPID is greater than the PID controller.